2021
DOI: 10.3926/jiem.3223
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of inventory management in footwear industry

Abstract: Purpose: The objective of this research was to implement new inventory management in a footwear company through the analysis of indicators obtained from inventory data collection.Design/methodology/approach: The methods of ABC analysis, demand forecasting, safety stock, reorder point and economic order quantity were applied. The items in inventory were classified by order of financial importance through ABC analysis, and the proposed indicators were analyzed to determine the moment the inventory replenishment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 6 publications
0
3
0
1
Order By: Relevance
“…Given the seasonality of demand for items in academic environments, it would be useful to create a DSS that uses information about the demand forecast to signal the moment and quantity of an order. Therefore, articles were reviewed on mathematical models that allow the calculation of the safety stock, considering demand forecasts [30][31][32][33].…”
Section: Perfectionmentioning
confidence: 99%
“…Given the seasonality of demand for items in academic environments, it would be useful to create a DSS that uses information about the demand forecast to signal the moment and quantity of an order. Therefore, articles were reviewed on mathematical models that allow the calculation of the safety stock, considering demand forecasts [30][31][32][33].…”
Section: Perfectionmentioning
confidence: 99%
“…With the cases studied in the use of this methodology applied in primary and non-primary manufacturing industries, it is concluded that a greater organization is generated by reducing the search times for articles and maintaining order and cleanliness of the area, ensuring the quantity that is stored to avoid the loss of these products, whether they are finished products or raw material [19].…”
Section: S In a Non-primary Manufacturermentioning
confidence: 99%
“…Es vital para las empresas contar con una gestión de pronósticos para la toma estratégica de decisiones, ya que con ello se logra un mayor desempeño en la organización con el uso de los diferentes modelos de pronósticos que existen anticipando el comportamiento de las variables, y visualizando la tendencia futura de la demanda [9]. La previsión de la demanda es fundamental para el estudio del inventario, debido a que informa en cantidad y en el tiempo indicado los productos que serán necesarios, además de ser un punto de partida para la planificación [10]. Cada uno de los modelos de pronósticos utilizan ciertas técnicas de pronósticos que ayudan a predecir la demanda de los productos en un escenario de producción: tendencia, ciclo, estacionalidad, aleatoriedad [11].…”
Section: Modelo De Pronósticounclassified